Model Learning Approach pada Mata Kuliah Basic Aircraft Material (BAM) di Perguruan Tinggi Vokasi Indonesia - Nur, Mulyadi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Basic Aircraft Materials (BAM) is a field of science that studies the basics of aircraft maintenance. The assessment system carried out in this course apart from UTS and UAS, is also based on the 2 tasks being carried out, and the attitude of the cadets while studying the BAM course. While the demands on this BAM course are that cadets are required to be able to analyze cases and carry out work practices. In order for the cadets to meet the demands of the BAM courses, the cadets have different approaches to learning. The results of the study found that in the learning of cadets with a surface approach, 40% of cadets stated that the course was important and 60% stated that the task given was a burden and only studied by focusing on the sub-subjects that were considered important. The conclusion with this learning method, then the learning outcomes of cadets are increasing.